(untitled) (Research, Society and Development, 2023)
Currently the state of Paraná is in first place in the country’s aquaculture production, and this production is concentrated in the Western region. Data from FAO indicate the continuous growth of the activity, and recent structural investments in the West region, such as the installation of the largest fish slaughterhouse in Brazil, show the regional trend of growth of aquaculture activity. The objective of this study was to diagnose, through data survey, the alevinating production in the micro region of Toledo. Previously, a survey on the quantity of existing active properties was carried out with ADAPAR and analysis of the production data from SEAB. The production of the micro region of Toledo is concentrated around tilapia, a species that, like the national level, is the production in the entire studied region. In the coming years the production should increase even more, mainly by expanding the facilities and attracting new cooperatives. Thus, creating new jobs in the rural areas and in the industry.